2016
DOI: 10.1016/j.jpain.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Some Words Hurt More Than Others: Semantic Activation of Pain Concepts in Memory and Subsequent Experiences of Pain

Abstract: Consistent with current theories of memory and pain, we found that high, relative to low activation of pain concepts in memory increased psychological and physiological responses to laser-induced pain. The effect remained regardless of whether participants showed conscious awareness of activation. Theoretical and clinical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 82 publications
5
16
0
1
Order By: Relevance
“…Research in chronic pain patients also supports experimental evidence coming from general population showing both higher levels in behavioral (i.e., augmented pain perception; Weiss et al, 2003 ) and electrophysiological responses (i.e., enhanced amplitudes of laser-evoked potentials-LEPs; Dillman et al, 2000 ; Price, 2000 ) to laser-painful stimulation during the processing of negative primes. From these results, several authors have suggested that pain-related semantic primes might pre-activate neural networks favoring pain memories and pain processing (Price, 2000 ; Brown, 2004 ; Swannell et al, 2016 ). According to this idea, a distributed neural network for pain memories is established in each individual's biographic memory system when is exposed repeatedly to painful experiences.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Research in chronic pain patients also supports experimental evidence coming from general population showing both higher levels in behavioral (i.e., augmented pain perception; Weiss et al, 2003 ) and electrophysiological responses (i.e., enhanced amplitudes of laser-evoked potentials-LEPs; Dillman et al, 2000 ; Price, 2000 ) to laser-painful stimulation during the processing of negative primes. From these results, several authors have suggested that pain-related semantic primes might pre-activate neural networks favoring pain memories and pain processing (Price, 2000 ; Brown, 2004 ; Swannell et al, 2016 ). According to this idea, a distributed neural network for pain memories is established in each individual's biographic memory system when is exposed repeatedly to painful experiences.…”
Section: Introductionmentioning
confidence: 79%
“…According to this idea, a distributed neural network for pain memories is established in each individual's biographic memory system when is exposed repeatedly to painful experiences. Such pain network strengths its connections and increases its efficacy whenever a subject is exposed to painful stimulation (Swannell et al, 2016 ). Therefore, two different approaches would account for the emotional influences on pain modulation: (1) the motivational priming hypotheses—to generate an emotional negative state in the subject in which pain responses would be increased—and, (2) the activation of pain memories—it is assumed that the exposure to information about pain would create memory representations that are functionally equivalent to those encoded during episodes of pain themselves—(Meerman et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Il a aussi été démontré que l'utilisation de ''mots négatifs'' pouvait augmenter significativement la douleur ou l'anxiété des patients. 13,30 Par ailleurs, nous avons également montré que l'utilisation de l'hypnose conversationnelle consistant à associer la communication thérapeutique à la focalisation de l'attention du patient sur des événements agréables ou sur l'écran de l'échographe, permettait d'améliorer le confort des patients lors de la réalisation de blocs axillaires échoguidés. 31 L'amélioration du confort des patients s'explique probablement en partie par l'augmentation du tonus parasympathique lié à l'emploi des techniques de communication hypnotique, bien que cela n'ait pas été évalué ici.…”
Section: Discussionunclassified
“…The activation of a memory network for pain has been proposed as a potential explanation for this modulation [20,21]. In the case of chronic pain patients, repeated exposure to pain could establish and consolidate a pain memory network [16].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the activation of pain memories could occur under unconscious processes [20,23], this mechanism for inputting information in the cognitive system might influence different behaviours such as symptom experiencing (i.e. pain) without conscious awareness [21]. However, research on the emotional modulation of pain using experimental subliminal paradigms remains scarce, and its results mixed and contradictory.…”
Section: Introductionmentioning
confidence: 99%